Functionalized poly(pyrrole-3-carboxylic acid) nanoneedles for dual-imaging guided PDT/PTT combination therapy. (June 2018) - Liu, Xin; Su, Huiling; Shi, Wei; Liu, Yang; Sun, Yanan; Ge, Dongtao
Abstract: Herein, poly(pyrrole-3-carboxylic acid) (PPyCOOH) nanoneedles with abundant carboxyl groups were synthesized by aqueous dispersion polymerization method using pyrrole-3-carboxylic acid as conductive polymer monomer. The PPyCOOH nanoneedles not only owned good photothermal performance, but also more importantly showed enhanced tumor cell uptake efficiency (1.64 fold) compared with size and zeta-potential matched nanospheres. After loading photosensitizer aluminum phthalocyanine tetrasulfonate (AlPCS4 ) and modifying with poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) onto the PPyCOOH nanoneedles, novel nanoneedle complexes (AlPCS4 @PPyCONH-PAH-PAA) integrating photodynamic therapy (PDT) and photothermal therapy (PTT) were successfully fabricated. The as-prepared nanoneedle complexes improved uptake efficiency of AlPCS4 both in vitro and in vivo . Moreover, the nanoneedle complexes have infrared thermal and fluorescent properties. By combined PDT/PTT under the guiding of dual modal imaging, the tumors in mice were completely eliminated and no recurrence was observed in 30 days after treatment, indicating that PPyCOOH nanoneedles have great potential as a novel drug carrier for constructing multifunctional nanoplatform used for cancer treatment.